What do we do now? a workbook for the president-elect - Hess, Stephen (Brookings Institution Press, 2008)
"A workbook to guide future chief executives, decision by decision, through the minefield of transition. Based on experiences of a White House staffer and presidential adviser, shows what can be done to make presidential transitions go smoothly"--Provided by publisher.